Molecular, genetic and evolutionary analysis of a paracentric inversion in Arabidopsis thaliana. (13th September 2016) - Fransz, Paul; Linc, Gabriella; Lee, Cheng‐Ruei; Aflitos, Saulo Alves; Lasky, Jesse R.; Toomajian, Christopher; Ali, Hoda; Peters, Janny; van Dam, Peter; Ji, Xianwen; Kuzak, Mateusz; Gerats, Tom; et al.
Summary: Chromosomal inversions can provide windows onto the cytogenetic, molecular, evolutionary and demographic histories of a species. Here we investigate a paracentric 1.17‐Mb inversion on chromosome 4 of Arabidopsis thaliana with nucleotide precision of its borders. The inversion is created by Vandal transposon activity, splitting an F‐box and relocating a pericentric heterochromatin segment in juxtaposition with euchromatin without affecting the epigenetic landscape. Examination of the RegMap panel and the 1001 Arabidopsis genomes revealed more than 170 inversion accessions in Europe and North America. The SNP patterns revealed historical recombinations from which we infer diverse haplotype patterns, ancient introgression events and phylogenetic relationships. We find a robust association between the inversion and fecundity under drought. We also find linkage disequilibrium between the inverted region and the early flowering Col‐FRIGIDA allele. Finally, SNP analysis elucidates the origin of the inversion to South‐Eastern Europe approximately 5000 years ago and the FRI‐Col allele to North‐West Europe, and reveals the spreading of a single haplotype to North America during the 17th to 19th century. The 'American haplotype' was identified from several European localities, potentially due to return migration. Significance Statement: Structural rearrangements redefine chromosomes, shape genome diversity and can have profound effects on selection, adaptation and spread. Here we elucidate the history of a paracentric inversion in Arabidopsis thaliana, including its origin a few thousand years ago, its maintenance under certain environmental conditions and its migration patterns, from Europe to North America and back.